Bone density, balance and quality of life of postmenopausal women taking alendronate participating in different physical activity programs - Borba Pinheiro, Cláudio Joaquim; Alencar Carvalho, Mauro César Gurgel; Pereira Bezerra, Jani Cléria; Dantas, Estélio Henrique Martin; Janotta Drigo, Alexandre [UNESP]; Lima Silva, Nádia Souza (SAGE Publications, 2010)
Background: The objective of this study was to determine the effects of different physical activity (PA) programs on bone density, balance and quality of life of postmenopausal women taking concomitant alendronate. A quasi-experimental study was conducted with 35 volunteers divided into four groups: practitioners of resistance training (RTG, n = 9, 49.8±4.2 years), judo (JUG, n = 11, 52.2±5.3 years), water aerobics (WAG, n = 8, 57.1±7.4 years) and the control group (CG, n = 7, 53.8±4.4 years). Methods: The following assessment tools were used: bone mineral density (BMD) measured by dual X-ray absorptiometry of the spine and proximal femur, the ‘Osteoporosis Assessment Questionnaire’ (OPAQ) and the ‘Static Balance Test with Visual Control’. The physical activities were planned for 12 months in cycles with different intensities. A two-way analysis of variance (ANOVA) was used for analysis between groups, and a Scheffé post-hoc test was used for multiple comparisons. Results: The multiple comparisons results showed that the RTG and JUG groups were significantly more efficient in the variables studied, including: lumbar BMD (Δ% = 6.8%, p = 0.001), balance (Δ% = 21.4%, p = 0.01), OPAQ (Δ% = 9.1%, p = 0.005) and lumbar BMD (Δ% = 6.4%, p = 0.003), balance (Δ% = 14%, p = 0.02) and OPAQ (Δ% = 16.8%, p = 0.000) compared with the CG. Furthermore, the RTG (Δ% = 4.8%, p = 0.02) was significantly better than the WAG for the neck of femur BMD, and the JUG (Δ% = 16.8, p = 0.0003) also demonstrated superiority to the WAG in the OPAQ. Conclusions: The physical activities studied appear to improve BMD, balance and quality of life of postmenopausal women taking a bisphosphonate. In this small sample, the RTG and the JUG groups were superior to the other groups. © 2010, SAGE Publications. All rights reserved.
Keywords: bisphosphonate; bone density; exercise; menopause; postural balance; quality of life